Effects of Honey on Postprandial Hyperlipidemia and Oxidative Stress in Wistar Rats: Role of HMG-CoA Reductase Inhibition and Antioxidant Effect (Nigerian Journal of Physiological Sciences, 2021)
Summary: Postprandial hyperlipidemia is associated with oxidative stress and is an important risk factor for atherosclerosis and cardiovascular disease. The aims of this study were to investigate the antihyperlipidemic effect of honey administered 5 or 60 minutes before a high-fat diet (HFD), to explore the role of 3-hydroxy-3-methyl-glutaryl-coenzyme A (HMG-CoA) reductase in antihyperlipidemic effect of honey and to investigate the effect of honey on postprandial oxidative stress. Rats were fasted and randomized into 5 groups. Groups 1 and 2 were administered portable water. After 60 minutes, the groups were given portable water and HFD, respectively. Group 3 was administered honey. After 5 minutes, the rats were given HFD. Groups 4 and 5 were administered honey and simvastatin, respectively. After 60 minutes, the rats were given HFD. Four hours after portable water or HFD administration, the rats were sacrificed. Group 2 had significantly (p < 0.01) higher total cholesterol (TC), triglycerides (TG), low density lipoprotein (LDL) cholesterol, very low density lipoprotein (VLDL) cholesterol, catalase activity and significantly (p < 0.05) lower high density lipoprotein (HDL) cholesterol and HMG-CoA: mevalonate (p < 0.001) compared with Group 1. Group 3 had significantly (p < 0.01) higher TG and VLDL cholesterol and lower HMG-CoA: mevalonate compared with Group 1. Groups 4 and 5 exhibited significantly (p < 0.05 or p < 0.001) higher HDL cholesterol and HMG-CoA: mevalonate and lower LDL cholesterol compared with group 2. Honey pretreatment 60 minutes before HFD feeding exerts more significant antihyperlipidemic effect and attenuates more considerably postprandial hyperlipidemia-induced oxidative stress than honey administered 5 minutes before HFD in Wistar rats. This marked antihyperlipidemic effect of honey pretreatment is mediated in part via inhibition of HMG-CoA reductase